Relevance of Indirect Transmission for Wildlife Disease Surveillance - Lange, Martin; Kramer-Schadt, Stephanie; Thulke, Hans-Hermann (Frontiers in Veterinary Science, 2016)
Epidemiological models of infectious diseases are essential tools in support of risk assessment, surveillance design and contingency planning in public and animal health. Direct pathogen transmission from host to host is an essential process of each host-pathogen system and respective epidemiological modelling concepts. It is widely accepted that numerous diseases involve indirect transmission through pathogens shed by infectious hosts to their environment. However, epidemiological models largely do not represent pathogen persistence outside the host explicitly. We hypothesize that this simplification might bias management-related model predictions for disease agents that can persist outside their host for a certain time span. We adapted an individual-based, spatially explicit epidemiological model that can mimic both transmission processes. One version explicitly simulated indirect pathogen transmission through a contaminated environment. A second version simulated direct host-to-host transmission only. We aligned the model variants by the transmission potential per infectious host (i.e. basic reproductive number R0) and the spatial transmission kernel of the infection to allow unbiased comparison of predictions. The quantitative model results are provided for the example of surveillance plans for early detection of foot-and-mouth disease in wild boar, a social host. We applied systematic sampling strategies on the serological status of randomly selected host individuals in both models. We compared between the model variants the time to detection and the area affected prior to detection, measures that strongly influence mitigation costs. Moreover, the ideal sampling strategy to detect the infection in a given time frame was compared between both models. We found the simplified, direct transmission model to underestimate necessary sample size by up to one order of magnitude, but to overestimate the area put under control measures. Thus, the model predictions underestimated surveillance efforts but overestimated mitigation costs. We discuss parameterisation of indirect transmission models and related knowledge gaps. We conclude that the explicit incorporation of indirect transmission mechanisms in epidemiological modelling may reward by adapting surveillance and mitigation efforts.